Barriers to the dissemination of four harm reduction strategies: a survey of addiction treatment providers in Ontario - Cunningham John A; Hobden Karen L (BMC, 2006)
Abstract A sample of service providers at addictions agencies' in Ontario were interviewed by telephone to assess attitudes toward, anticipated internal and external barriers to implementing, and expected benefits of four harm reduction strategies: needle exchange, moderate drinking goals, methadone treatment, and provision of free condoms to clients. Respondents were also asked to define harm reduction, list its most important elements, and describe what they find most troubling and most appealing about harm reduction. Attitudes toward harm reduction in general and the services provided at each agency were also assessed. Results indicated that the service providers surveyed had positive attitudes toward each of the four harm reduction strategies and harm reduction in general, and the majority of respondents were aware of the benefits associated with each strategy. Almost all of the agencies surveyed allowed for moderate drinking outcomes in the treatment of alcohol problems, and most agencies provided free condoms to clients. In terms of barriers, anticipated negative community reaction to needle exchange, methadone treatment, and free condoms was a major concern for the majority of respondents. Lack of staff, of funding, or anticipated staff resistance were also cited as potential barriers to introducing these strategies. In the case of methadone maintenance, the unavailability of a qualified physician was listed as the primary constraint. Implications for future efforts directed at encouraging the adoption of these strategies and suggestions for future research are discussed.